Pulmonary actinomycosis affecting chest wall: a case report - Hassan, Md. Zakiul; Uddin, Md. Nazim; Ahsan, H. M. Nazmul (Bangladesh Journal of Medical Science, 2015)
Thoracic actinomycosis is an uncommon, chronic suppurative bacterial infection caused by Actinomyces species. Thoracic actinomycosis represents about one-fourth of all cases of actinomycosis. We report a case of left sided pleural effusion with hydropneumothorax with collapse and consolidation of left lung with discharging sinus in the left anterior chest wall. Actinomycosis was suspected and confirmed by microscopic identification of sulfur granules in the discharge of the sinus tract and also identification of gram-positive filamentous bacteria in the specimen of discharging sinus. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.417-41